EFFECT OF COMMUNICATION, DISCIPLINE, WORK ENVIRONMENT ON MPLOYEE PERFORMANCE AT KSP CU. MAKMUR BERSAMA - Christin Natalia Sianipar; Evi Irene Saurina Tampubolon (Bajang Institute, 2022)
This study aims to determine how the influence of communication, discipline, work environment on employee performance. The data processing technique used multiple regression analysis. The results of the hypothesis test state that: Hypothesis 1 is accepted, then communication has an effect on employee performance. Hypothesis 2 is accepted, then discipline has an effect on employee performance. Hypothesis 3 is accepted, then the work environment variable has an effect on employee performance. Hypothesis 4 is accepted, then the communication, discipline, and work environment variables have a simultaneous (simultaneous) effect on employee performance variables. This research is a replication of previous research where the difference lies only in the object under study.